2014
DOI: 10.1177/1535370214548995
|View full text |Cite
|
Sign up to set email alerts
|

Detection of urinary podocytes and nephrin as markers for children with glomerular diseases

Abstract: The purpose of this study was to detect the urinary podocytes and its related protein, nephrin, in the urine of the children with glomerular disease in order to analyze the relationship of the clinical testing with the significance of the glomerular disease. A total of 65 children with nephrotic syndrome were selected for this study. The podocytes and nephrin were detected in the urinary sediment by indirect immunofluorescence, enzyme-linked immunosorbent assay, and Western blotting. The urinary podocytes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 17 publications
(14 reference statements)
2
17
0
Order By: Relevance
“…This raises an important issue: how can physicians determine if active podocyte loss is taking place in their patients? While a definitive answer is not available, an interesting alternative may be found in the analysis of urinary markers of podocyte loss (32)(33)(34). However, we believe there is a growing need for the development of noninvasive methods to assess podocyte loss.…”
Section: Discussionmentioning
confidence: 99%
“…This raises an important issue: how can physicians determine if active podocyte loss is taking place in their patients? While a definitive answer is not available, an interesting alternative may be found in the analysis of urinary markers of podocyte loss (32)(33)(34). However, we believe there is a growing need for the development of noninvasive methods to assess podocyte loss.…”
Section: Discussionmentioning
confidence: 99%
“…Nephrin exists in podocytes and enters the urine in response to podocyte injury [11, 14-17]. The significantly higher concentration of uNep in AKI neonates demonstrates the presence of podocyte injury in neonates with AKI.…”
Section: Discussionmentioning
confidence: 99%
“…The protein markers in podocytes can be excreted in urine in the presence of podocyte injury, and the increased concentrations of nephrin in urine may reflect early glomerular injury [11-13]. To date, most studies of urinary nephrin (uNep) have been conducted in patients who have kidney disease with podocyte dysfunction, such as lupus nephritis, and have investigated the association of uNep with various renal traits [14-17]. The clinical utility of uNep for the detection of AKI in patients has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have explored biomarkers in serum and urine for MesPGN. It was reported that podocytes and nephrin in the urinary sediment and urinary transferrin were useful markers in children with glomerular disease . Kalantari et al.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have explored biomarkers in serum and urine for MesPGN. It was reported that podocytes and nephrin in the urinary sediment and urinary transferrin were useful markers in children with glomerular disease [2,3]. Kalantari et al found that differentially excreted candidate urinary proteins had potential as prognostic biomarkers for IgA nephritis [4].…”
Section: Introductionmentioning
confidence: 99%